2019
DOI: 10.7196/samj.2019.v109i12.013893
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low serum testosterone levels among men with type 2 diabetes mellitus attending two outpatient diabetes clinics in KwaZulu-Natal Province, South Africa

Abstract: Corresponding author: I M Paruk (paruki@ukzn.ac.za) Background. The reported prevalence of low testosterone among men with type 2 diabetes mellitus (T2DM) is high. However, there is a dearth of information on the prevalence of androgen deficiency symptoms and low serum testosterone levels in men with T2DM from sub-Saharan Africa. Scanty data are available from Nigeria, Ghana and South Africa (SA). Objectives. To determine the prevalence of low serum testosterone and associated risk factors and the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The prevalence of hypogonadism in men with T2DM was statistically significantly higher than in the controls. Studies from Nigeria and South Africa, compared to this study, reported a lower prevalence of hypogonadism or low serum total testosterone in men with T2DM [15][16][17]25]. In Nigeria, Ogbera et al reported the prevalence of hypogonadism among men with T2DM to be 36% at General Hospital Gbagada, Lagos.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…The prevalence of hypogonadism in men with T2DM was statistically significantly higher than in the controls. Studies from Nigeria and South Africa, compared to this study, reported a lower prevalence of hypogonadism or low serum total testosterone in men with T2DM [15][16][17]25]. In Nigeria, Ogbera et al reported the prevalence of hypogonadism among men with T2DM to be 36% at General Hospital Gbagada, Lagos.…”
Section: Discussionmentioning
confidence: 41%
“…In comparison, Onung et al reported a prevalence of 38.9% in Lagos and Ugwu et al reported a prevalence of 52.5% in Ile-Ife [15][16][17]. Paruk et al reported the prevalence of low serum total testosterone in men with T2DM to be 35.8% [25]. Tan et al reported a prevalence of hypogonadism among elderly diabetics to be 64%; however, the effect of advancing age on testosterone levels could have been a confounding factor [28].…”
Section: Discussionmentioning
confidence: 99%
“…In cross-sectional studies, between 20-80.4% of men with T2DM have hypogonadism [ 3 - 5 ]. Type 2 diabetes mellitus has been reported to be associated with low testosterone [ 3 , 6 - 9 ]. Low testosterone levels are reportedly associated with a high risk of developing T2DM in men, a sequel to its insulin-resistance effect [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now obvious that the functions of testosterone extend well beyond the sexual domain, especially in men, affecting both physiological and mental aspects of life. Hypogonadism is widespread and inevitable; however, it is difficult to conduct studies to ascertain the full extent of testosterone influence, which has been hypothesized to play a role in a range of common metabolic, immune and psychiatric diseases [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aim to determine the effect of testosterone on previously associated common diseases, namely, type II diabetes (T2D), rheumatoid arthritis (RA), gout, depression, bipolar disorder (BP), schizophrenia (SCZ) and Alzheimer’s disorder (AD) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], by conducting a two-sample Mendelian randomization study in an effort to determine whether testosterone could potentially play a causative role in these disorders. To our knowledge, this is the first Mendelian randomization study looking into the relationship between testosterone and common diseases.…”
Section: Introductionmentioning
confidence: 99%